Identifying Patterns and Predictors of Prescription Opioid Use After Total Joint Arthroplasty. Issue 5 (3rd May 2021) - Chaudhary, Muhammad Ali; Dalton, Michael K; Koehlmoos, Tracey P; Schoenfeld, Andrew J; Goralnick, Eric
ABSTRACT: Introduction: Total hip arthroplasty and total knee arthroplasty account for over 1 million procedures annually. Opioids are the mainstay of postoperative pain management for these patients. In this context, the objective of this study was to determine patterns of use and factors associated with early discontinuation of opioids after total joint arthroplasty (TJA). Methods: TRICARE claims data (2006-2014) were queried for adult (18-64 years) patients who underwent total hip arthroplasty or total knee arthroplasty. Prescription opioid use was identified from 6 months before and 6 months after surgical intervention. Prior opioid use was categorized as naïve, exposed (with non-sustained use), and sustained (6 month continuous use before surgery). Cox proportional-hazards models were used to identify factors associated with opioid discontinuation following TJA. Results: Among the 29, 767 patients included in the study, 15, 271 (51.3%) had prior opioid exposure and 3, 740 (12.5%) were sustained opioid users. At 6 months after the surgical intervention, 3, 171 (10.6%) continued opioid use, 3.3% were among opioid naïve, 10.2% among exposed, and 33.3% among sustained users. In risk-adjusted models, prior opioid exposure (hazards ratio: 0.65, 95% CI: 0.62-0.67) and sustained prior use (hazards ratio: 0.33, 95% CI: 0.31-0.35) were the strongest predictors of lower likelihood of opioid discontinuation. Lower socio-economic status, depression, and anxiety were also strong predictors. Conclusion: Prior opioid exposure was strongly associated with continued opioid dependence after TJA. Although one-third of prior sustained users continued use after surgery, approximately 10% of previously exposed patients became sustained users, making them the prime candidates for targeted interventions to reduce the likelihood of sustained opioid use after TJA.